The Thoughts of Abdur Rauf Al-Singkili's Hadith on the Formation of Academic Traditions in Aceh at the 17th Century - Lisa Mawarda; Ida Rochmawati (Universitas Islam Negeri Sumatera Utara, 2026)
This study aims to analyze the hadith thought of Abdur Rauf al-Singkili and its influence on the formation of academic traditions in Aceh in the 17th century. The problem raised in this study is how the hadith thought of Abdur Rauf al-Singkili, combined with the teachings of Sufism, was able to form a moderate and distinctive Acehnese educational approach and contribute to the development of academic traditions. The method used in this study is qualitative with the type of library research. In addition, this study uses historical analysis and Karl Mannheim's theory of sociology of knowledge to reveal how the social, cultural, and political contexts of the time influenced the thoughts and intellectual activities of Abdur Rauf al-Singkili. The results of the study indicate that the hadith thought of Abdur Rauf al-Singkili played a strategic role in building academic traditions in Aceh through the dissemination of hadith knowledge that is moderate, integrative and inclusive. This contribution not only strengthens hadith studies, but is also able to address socio-political issues at that time, while forming a broader scientific network in the archipelago. The perspective of Karl Mannheim's sociology of knowledge theory emphasizes that Abdur Rauf al-Singkili's thoughts were born from the religious, heterogeneous and dynamic social conditions of Aceh, and were influenced by intellectual interactions with Middle Eastern scientific traditions and the needs of local society.